2016
DOI: 10.3126/jmcjms.v3i1.15369
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vitamin D in children with pneumonia: a randomized control trial study

Abstract: Background and Objectives:Pneumonia is the inflammation of parenchyma of lungs. It strictly represents any inflammatory condition that involves the lungs along with the visceral pleura, airways, alveoli, connective tissues and vascular structures. The objective of the study was to see the efficacy of vitamin D in children with pneumonia. Material and Methods:A randomized control study was conducted in Department of Pediatric Medicine, Mayo Hospital, Lahore, Pakistan. One hundred patients with pneumonia receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
0
15
1
Order By: Relevance
“…A possible explanation could be, only a subgroup of study children might have been benefitted from vitamin D supplementation, whereas the effect of vitamin D supplementation was obscured in children having severe vitamin D deficiency [ 41 ]. This is in contrast to the studies in Kabul and Pakistan in which vitamin D supplementation resulted in a reduction of pneumonia incidence within one and three months subsequent to hospital discharge [ 30 , 38 ]. The difference in this regard between these studies and our might be explained by differences in the study populations.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…A possible explanation could be, only a subgroup of study children might have been benefitted from vitamin D supplementation, whereas the effect of vitamin D supplementation was obscured in children having severe vitamin D deficiency [ 41 ]. This is in contrast to the studies in Kabul and Pakistan in which vitamin D supplementation resulted in a reduction of pneumonia incidence within one and three months subsequent to hospital discharge [ 30 , 38 ]. The difference in this regard between these studies and our might be explained by differences in the study populations.…”
Section: Discussioncontrasting
confidence: 81%
“…Only two studies [ 26 , 38 ] including ours have included information on malnutrition, which was present in approximately 60% in both the groups in our study. Moreover, approximately 50% children in both the groups in our study were vitamin D deficient.…”
Section: Discussionmentioning
confidence: 99%
“…These observational findings have laid the foundation for clinical trials of vitamin D supplementation for treatment or prevention of childhood respiratory tract infections, as shown in Table 6 a,b [ 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Of these, 2 studies 33,35 reported the code key would be opened only after administration of the intervention, duration of follow-up, data collection, and tabulation were completed, thus preventing detection bias; these studies were assessed as being at low risk of bias for this domain. Five studies 34,38,39,41,42 did not describe methods to prevent detection bias and were assessed as being at unclear risk of bias. However, Somnath et al 43 were unblinded, presenting a high risk of performance bias.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
“…For the present meta-analysis, our search identified a total of 282 studies that were assessed for eligibility; of these, 13 studies 28,29,[33][34][35][36][37][38][39][40][41][42][43] with a total of 4786 randomized participants fulfilled the eligibility criteria (Figure 1). Although Full-text articles excluded, with reasons (n = 19):…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%